The Fifth Census - The 1830 Census - Charles County, Maryland - Schuhart, Wanda (Transcriber and Indexed); Mary Beavan (Transcriber and Indexed) (Printing Press Leonardtown, MD, 2001)
Transcribed and Indexed by Wanda Schuhart and Mary Beavan for St. Mary's County Historical Society